PENGARUH DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA CV ARTHA LARAS JAYA KOTA TANGERANG - Nurul Khotijah Malitasari; Ahmad Nazir (Journal of Research and Publication Innovation, 2025)
This research is titled "The Influence of Work Discipline and Job Satisfaction on Employee Performance CV Artha Laras Jaya in Tangerang City." The purpose of this study is to determine the effect of work discipline and job satisfaction on employee performance at CV Artha Laras Jaya in Tangerang City. This research is quantitative in nature. The analytical methods used in this study include validity tests, reliability tests, classical assumption tests, descriptive analysis, simple linear regression tests, multiple linear regression tests, correlation coefficient tests, determination coefficient tests, t-tests, and F-tests. The population in this study is CV Artha Laras Jaya in Tangerang City, with a saturated sample of 52 respondents. The results of this study, based on the determination coefficient, indicate that work discipline and job satisfaction contribute 0.678 or 67.8% to employee performance, while the remaining 32.2% is influenced by other variables not examined. The results show the multiple linear regression equation Y = 6.552 + 0.743 X1 + 0.100 X2. The correlation coefficient for Work Discipline (X1) against Performance (Y) is 0.820, meaning there is a very strong relationship between the two variables, while the correlation coefficient for Job Satisfaction (X2) against Performance (Y) is 0.659, indicating a strong relationship. The results of the simultaneous effect test of the independent variables on the dependent variable show that Fcount = 51.759 > Ftable = 3.18, leading to the conclusion that both partially and simultaneously, there is an effect of Work Discipline and Job Satisfaction on Employee Performance at CV Artha Laras Jaya in Tangerang City.